1998
DOI: 10.1046/j.1365-4362.1998.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotin recycling impairment in phenylketonuric children with seborrheic dermatitis

Abstract: It is suggested that the high biotin levels in group A patients reflect the intake of water-soluble biotin of vegetable origin. In contrast, the low biotinidase activity in group B patients may be attributed to their high Phe plasma levels, which acts as an enzyme inhibitor, as shown by the in vivo and in vitro results. Consequently, the observed seborrheic dermatitis in PKU children (group B) is associated with an impairment of biotin recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…A study reported that high phenylalanine levels can inhibit biotinidase activity, causing some skin conditions [20], but the association between the two has not been examined. Observational data from NBS Connect, may support this hypothesis and the need for additional research is indicated to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that high phenylalanine levels can inhibit biotinidase activity, causing some skin conditions [20], but the association between the two has not been examined. Observational data from NBS Connect, may support this hypothesis and the need for additional research is indicated to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published from 1994 [38] to 2023 [39], and their characteristics are detailed in Table 1. Four studies were conducted in Greece [25,27,40,41], three in Turkey [31,42,43], three in Spain [32,44,45], two in Austria [26,46], two in Chile [39,47], two in Japan [29,30], two in the United Kingdom [48,49], two in the USA [38,50], and one each in Germany [51], France [52], Poland [28], and Switzerland [53]. All studies, except for one case-control study [26], were cross-sectional and compared individuals with PKU to healthy controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies assessed children [25,27,28,31,40], one studied adolescents [43], children and adolescents were included in nine studies [26,32,38,41,42,45,46,50,51,53], six studies examined adults [29,30,39,48,49,52], and the remaining two studies had a mixed population [44,47]. Most studies included males and females [24,[26][27][28][29][30]37,38,[40][41][42]45,46,[49][50][51][52], and while it was not explicitly stated in other studies [25,27,40,44,45,48,49], they likely involved both male and female participants. Table 2<...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotin (B7) is used for the treatment of diabetes [123] and in the prevention of some birth defects [124]. It plays a vital role in the treatment of cholesterol [125], brittle fingernails [126], seborrheic dermatitis [127], and hair loss.…”
Section: Functionmentioning
confidence: 99%